2023
DOI: 10.1021/jacs.3c06335
|View full text |Cite
|
Sign up to set email alerts
|

Proton- versus Cation-Selective Transport of Saccharide Rim-Appended Pillar[5]arene Artificial Water Channels

Iuliana M. Andrei,
Wenzhang Chen,
Marc Baaden
et al.

Abstract: Transport of water across cell membranes is a fundamental process for important biological functions. Herein, we focused our research on a new type of symmetrical saccharide rim-functionalized pillar[5]­arene (PA-S) artificial water channels with variable pore structures. To point out the versatility of PA-S channels, we systematically varied the nature of anchoring/gate keepers d-mannoside, d-mannuronic acid, or sialic acid H-bonding groups on lateral pillar[5]­arene (PA) arms, known as good membrane adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…With the development of advanced characterization techniques, the complex structures of natural sodium channels have gradually been resolved, of which the selectivity filters determine the ion selectivity for sodium ions. In fact, the selective filter structures of natural sodium channels exhibit significant diversity within different physiological environments, and thus display distinct Na + /K + ion selectivity ( P Na/K ) ratios ranging from 12 to 50. The complex structure and utilization difficulties of natural sodium channels severely restrict their applications in life systems, and the manufacture of artificial channels with concise structures and excellent performance will provide an alternative approach to compensate for functional deficiencies of natural ion channels. As the counterpart of intracellular sodium ions, artificial channels that selectively transport K + , such as supramolecular, unimolecular, and even carriers have been widely explored. For instance, biomimetic potassium channels based on helical foldamers with ion selectivity of up to P Na/K = 32 have been developed by us recently . Moreover, we found that the lumen size of 2.5 Å is the critical size for the transformation of ion selectivity between potassium and sodium ions .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of advanced characterization techniques, the complex structures of natural sodium channels have gradually been resolved, of which the selectivity filters determine the ion selectivity for sodium ions. In fact, the selective filter structures of natural sodium channels exhibit significant diversity within different physiological environments, and thus display distinct Na + /K + ion selectivity ( P Na/K ) ratios ranging from 12 to 50. The complex structure and utilization difficulties of natural sodium channels severely restrict their applications in life systems, and the manufacture of artificial channels with concise structures and excellent performance will provide an alternative approach to compensate for functional deficiencies of natural ion channels. As the counterpart of intracellular sodium ions, artificial channels that selectively transport K + , such as supramolecular, unimolecular, and even carriers have been widely explored. For instance, biomimetic potassium channels based on helical foldamers with ion selectivity of up to P Na/K = 32 have been developed by us recently . Moreover, we found that the lumen size of 2.5 Å is the critical size for the transformation of ion selectivity between potassium and sodium ions .…”
Section: Introductionmentioning
confidence: 99%
“…Pillar­[ n ]­arenes, a class of macrocyclic host molecules with a distinctive pillar-shaped architecture, exhibit remarkable host–guest interactions, enabling them to complex with a diverse range of guest molecules. Their significant properties stem from their unique structural features, rendering them promising candidates for various applications in supramolecular chemistry. Modifiable functionalities and unique structural characteristics of pillar­[ n ]­arenes hold promise for developing materials specifically tailored for biological applications. Pillar­[ n ]­arenes have been shown to possess inherent antimicrobial properties against a broad range of planktonic bacteria, including both Gram-positive and Gram-negative strains. , Biocompatibility and safety are the essential aspects of any potential anti-biofilm agents for human use. Preliminary investigations suggest pillar­[ n ]­arenes and their derivatives as safe and biocompatible agents; hence they exhibit low cytotoxicity and minimal adverse effects. The unique properties of pillar­[ n ]­arenes extend beyond their antimicrobial potential, encompassing artificial transmembrane transport capabilities. Pillar­[ n ]­arene derivatives possess the capacity to facilitate the transport of specific molecules across cell membranes. This notable feature holds significant implications for drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by biological receptors, numerous supramolecular macrocycles were studied through conventional molecular docking by using computational and simulation methods 23 27 . Prominent examples of such supramolecular macrocycles include cucurbiturils 28 33 and pillar[n]arenes 34 39 , which exhibit exceptional host-guest binding capabilities due to their well-defined and complementary structures that can effectively encapsulate and interact with specific guest molecules. The identification of a specific binding mode by molecular docking based on the computational method elucidated structural compatibility between supramolecular macrocycles and guests.…”
Section: Introductionmentioning
confidence: 99%